The relationship between human capital investment and economic development in Sabah - Kasim Md Mansur; Nurul Arfa Mat; Roslinah Mahmud (Penerbit Universiti Malaysia Sabah, 2015)
This research analyzes the effects of human capital investment on education, health and migration to economic development in Sabah. Extended augmented Solow growth model theory is utilized in this research. This study uses time series data from 1980 to 2010. Ordinary Least Square (OLS) regression analysis is employed using Eviews 6.0 version software. Regression shows higher gross domestic product (GDP) per capita influenced by better literacy rate, longevity of life expectancy at birth and required number of immigrants with a sustainable gross domestic savings and improvement in unemployment rate. Empirical tests of theoretical hypothesis produce results that are consistent with the conclusion in this study.